New Data on the Signal Flies of the Genus Platystoma (Diptera, Platystomatidae) in the Fauna of Iran Platystoma - Mohamadzade Namin, S. (Вестник зоологии, 2011)
As a result of studies of the signal flies in Iran, 5 species of the genus Platystoma Meigen (P. chrysotoxum Hendel, P. dimidiatum Hendel, P. elegans Hendel, P. pubescens Loew and P. rufipes Meigen) are recorded for the first time for Iranian fauna.